Investigating the urban eco-environmental quality utilizing remote sensing based approach: evidence from an industrial city of Eastern India - Sharmistha Mondal; Kapil Kumar Gavsker (Discover Applied Sciences)
Abstract Urbanization, coupled with industrialization, leads to both economic growth and exponential urban growth, resulting in deteriorating environmental quality in urban areas, which poses a significant threat to the sustainability of cities. Hence, to restore biodiversity and ensure regional sustainability, it is necessary to immediately evaluate the eco-environmental quality of urban areas. The present research investigates the spatio-temporal changes in urban eco-environmental quality of the Asansol industrial city using an integrated ‘Urban Eco-Environmental Index’ (UEEQI) developed utilizing the Google Earth Engine platform and a remote sensing-based approach. The study used four spectral indices, including Normalized Difference Vegetation Index (NDVI), Modified Normalized Difference Water Index (MNDWI), Normalized Difference Built-up Index (NDBI), Normalized Difference Bareness Index (NDBaI), along with Land Surface Temperature (LST) (as a thermal index), derived from the remote sensing data to measure environmental quality. Global Moran’s I and LISA were used to quantify spatial autocorrelation, showing the clustering of similar values or outliers of UEEQ within geographic space. The findings showed that high mean values of NDBI and NDBaI contributed to a lower mean UEEQI value of 0.38 in 2021 compared to previous decades. The spatio-temporal distribution of UEEQI showed that the ‘Very Poor’ category had grown from 0.06% in 1991 to 2% in 2021, while the ‘Poor’, ‘Good’, and ‘Excellent’ categories had declined. Over the 30 years, the UEEQI showed a rising trend of ‘Highly Degraded’ and ‘Degraded’ areas while decreasing the trend of ‘Improved’ or ‘Highly Improved’ environmental quality in the city. Moran’s scatter plot illustrated a highly positive clustered pattern of UEEQ across the city. Hotspots were mainly found in urbanized areas that had an “Average” urban eco-environment quality. Conversely, areas covered with bare surfaces, fallow lands, and brickfields were recognized as Coldspots. This study is crucial for determining specific regions of declining environmental quality and encourages local authorities and decision-makers to integrate eco-environmental conservation zones into city planning to foster healthier, more resilient, and sustainable cities.